A conceptual modeling of ecological greywater recycling system in Kuching city, Sarawak, Malaysia - Mah, Yau Seng; Frederik Josep, Putuhena; Hin, Charles Joo Bong (Elsevier, 2008)
A pilot project of greywater ecological treatment is established in Kuching city since 2003. Such treatment facility opens up an opportunity of wastewater reclamation for reuse as secondary sources of water for non-consumptive purposes. This paper aims in exploring the potential of the intended purposes in the newly developed ecological treatment project. The modeling process of using a mathematical representation of the real system is commonly performed to evaluate a proposed system. By using network simulations, which replicate the dynamics of a proposed system, problems can be anticipated and solutions can be evaluated before time, money and materials are invested in a real-world project. Efforts are made to carry out a hydraulic modeling of a hypothetical greywater recycling system as an integrated part of the Kuching urban water supply using theWallingford Software model, InfoWorksWater Supply (WS). The modeling efforts where the greywater is treated, recycled and reused in the domestic environment have shown water saving of about 40%. This model assists the researcher to evaluate the performance of the recycling system in the context of shifting towards more integrated water resources management.